Long non-coding RNA XIST promotes cell growth by regulating miR-139-5p/PDK1/AKT axis in hepatocellular carcinoma - Yichao Mo; Yaoyong Lu; Peng Wang; Simin Huang; Longguang He; Dasheng Li; Fuliang Li; Junwei Huang; Xiaoxia Lin; Xueru Li; Siyao Che; Qinshou Chen (Tumor Biology, 2017)
Abnormal expression of long non-coding RNA often contributes to unrestricted growth of cancer cells. Long non-coding RNA XIST expression is upregulated in several cancers; however, its modulatory mechanisms have not been reported in hepatocellular carcinoma. In this study, we found that XIST expression was significantly increased in hepatocellular carcinoma tissues and cell lines. XIST promoted cell cycle progression from the G1 phase to the S phase and protected cells from apoptosis, which contributed to hepatocellular carcinoma cell growth. In addition, we revealed that there was reciprocal repression between XIST and miR-139-5p. PDK1 was identified as a direct target of miR-139-5p. We proposed that XIST was responsible for hepatocellular carcinoma cell proliferation, and XIST exerted its function through the miR-139-5p/PDK1 axis.